How Best to Perform Co-Research With Children and Adolescents: A Rapid Qualitative Evidence Synthesis - Karolina Seidl; Anna Wahl; Daniela Rojatz; Lisa Affengruber; Isolde Sommer; Irma Klerings; Lisa Gugglberger; Rosie Nash; Johanna Mahr-Slotawa; Ursula Griebler (International Journal of Qualitative Methods)
In recent years, emphasis has grown on involving children and adolescents in research. Co-research allows these age groups to be equal partners in research, ensures that their perspectives and experiences are considered, and empowers them to express their views and expertise on their own lives. However, involving children and young people in co-research poses complex challenges and raises multifaceted issues. This review provides insights from previous co-research processes and outlines the characteristics of an ideal co-research process. A rapid qualitative evidence synthesis was conducted to synthesize the qualitative research on co-research experiences with children and adolescents. We searched three electronic databases up to May 2023 and carried out supplementary searches. Two reviewers screened 742 abstracts and 169 full-text articles to select studies that met our eligibility criteria. From 48 eligible studies, we sampled 30 to synthesize based on the data richness for qualitative content analysis. Our synthesis highlights key factors that are crucial in co-research processes with children and adolescents. We developed a framework consisting of six key themes: the sociocultural factors, ethics, setting factors, project management, interpersonal factors, and individual factors of the young co-researchers. These themes involve various factors (e.g., children’s and adolescents’ rights, power imbalances, support structures, remuneration/incentives, trust, and time availability) that must be considered. The challenges and facilitators encountered throughout the co-research process were synthesized. In addition, we provide an overview of targeted co-research methods for young age groups, which offers valuable guidance for future co-research initiatives.